Analisis pemanfaatan shopee paylater sebagai alat pinjaman online di era pasca pandemic covid-19 - Monabila Magelo; Tessalonika Sinaga; Erwin Permana (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
Rapid developments in the digital world have penetrated various sectors including the financial sector with the emergence of financial technology (fintech). Its development accelerated when the Covid-19 pandemic occurred, thus forming the habit of online transactions. The impact of shifting people's shopping habits from face-to-face to online is due to the many conveniences offered by online retailers. Even though the pandemic is now over, the habit of online shopping persists. Consumers are also increasingly spoiled by the various business models offered by business people. One of them is the later payment offered by Shopee with the Shopee Paylater brand. This study aims to analyze the use of shopee paylater as an online loan tool in the post-Covid-19 pandemic era. The research was conducted with a qualitative approach. The data was obtained through observing various shopping patterns using the shopee paylater. Then presented in a descriptive way. The results show that the general public uses the Shopee Paylater feature at Shopee so they can still shop online with a